ANALISIS PARTISIPASI IBU BALITA DALAM PEMANFAATAN POSYANDU DI KELURAHAN BARU KECAMATAN REBO JAKARTA TIMUR - Okta Zenita Siti Fatimah; Seventina Nurul Hidayah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Posyandu is a form of Community Based Health Efforts to empower and facilitate the community in obtaining basic health services to accelerate the decline in MMR and infants/toddlers. The visits of mothers of children under five to the posyandu in Kelurahan Baru are still low at 41%. The purpose of the study was to analyze the participation of mothers under five in the use of posyandu in Pasar Rebo District, East Jakarta in 2019. This type of research was a descriptive study with a cross sectional approach. The population in this study were all mothers who had toddlers, totaling 241 mothers. The sample is 78 mothers of toddlers. The sampling technique was by multistage random sampling. The results of the study showed that respondents who used posyandu well were 73%, most of the work mothers did not work by 86%, respondents who had good knowledge were 85%, respondents who received good support from their families/husbands were 68%, respondents who received good support both from health workers by 77%, respondents who received good support from cadres by 83%, supporting infrastructure facilities by 85%. The majority of mothers make good use of posyandu. Factors that influence the use of posyandu are employment, knowledge, support from health workers, cadre support, husband/family support and the availability of infrastructure. Keywords : participation of community, health of mother and child